Looking for Alibrandi - Marchetta, Melina, 1965- (New York : Orchard Books, 1999)
During her senior year in a Catholic school in Sydney, Australia, seventeen-year-old Josie meets and must contend with the father she has never known.
Keywords: Fathers and daughters -- Fiction; Catholic schools -- Fiction; High schools -- Fiction; Schools -- Fiction; Sydney (N.S.W.) -- Fiction; Australia -- Fiction